Analisa Bantuan Luar Negeri Inggris dalam Skema Kerjasama Multistakeholder Forestry Program 3 di Jepara - Himalia, Mia Risa; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Jepara is one of the biggest sector on furniture products in Indonesia. The Quality ofJepara furniture product has grown to various parts of the world. England is one of thebiggest consumer of Jepara furniture products and Europe is part of the cunsomers too.The High export rates of furniture was not comparable with the implementation of SVLKwhich has been agreed between Indonesi and Europe. Jepara was not maximally in theimplementation of SVLK then England with initiatively to provide the assistance to Jeparathrough the scheme of cooperation with MFP 3 that runs in 2014-2016. The researchmethode used is qualitative explaining what the motive of England in providing assistanceto Jepara. Then that motive is analyzed to find the facts behind the attitude from England.To answer the phenomenon, the research using the theory of constructivism. Teh resultshow that the underlying motives of England on providing assistance to Jepara is purely tohelp Jepara in SVLK ownership, beside that is a concrete act assistance of England whichhave the commitment to environment.